Preclinical Evaluation of 4-Methylthiobutyl Isothiocyanate on Liver Cancer and Cancer Stem Cells with Different p53 Status - Lamy, Evelyn; Hertrampf, Anke; Herz, Corinna; Schüler, Julia; Erlacher, Miriam; Bertele, Daniela; Bakare, Adekunle; Wagner, Meike; Weiland, Timo; Lauer, Ulrich; Drognitz, Oliver; Huber, Roman; et al. (PLOS ONE, 2013)
Isothiocyanates from plants of the order Brassicales are considered promising cancer chemotherapeutic phytochemicals. However, their selective cytotoxicity on liver cancer has been barely researched. Therefore, in the present study, we systematically studied the chemotherapeutic potency of 4-methylthiobutyl isothiocyanate (MTBITC). Selective toxicity was investigated by comparing its effect on liver cancer cells and their chemoresistant subpopulations to normal primary hepatocytes and liver tissue slices. Additionally, in a first assessment, the in vivo tolerability of MTBITC was investigated in mice. Growth arrest at G2/M and apoptosis induction was evident in all in vitro cancer models treated with MTBITC, including populations with cancer initiating characteristics. This was found independent from TP53; however cell death was delayed in p53 compromised cells as compared to wt-p53 cells which was probably due to differential BH3 only gene regulation i. e. Noxa and its antagonist A1. In normal hepatocytes, no apoptosis or necrosis could be detected after repeated administration of up to 50 µM MTBITC. In mice, orally applied MTBITC was well tolerated over 18 days of treatment for up to 50 mg/kg/day, the highest dose tested. In conclusion, we could show here that the killing effect of MTBITC has a definite selectivity for cancer cells over normal liver cells and its cytotoxicity even applies for chemoresistant cancer initiating cells. Our study could serve for a better understanding of the chemotherapeutic properties of isothiocyanates on human liver-derived cancer cells.